2009
DOI: 10.46298/dmtcs.2734
|View full text |Cite
|
Sign up to set email alerts
|

Matroid Polytopes and Their Volumes

Abstract: International audience We express the matroid polytope $P_M$ of a matroid $M$ as a signed Minkowski sum of simplices, and obtain a formula for the volume of $P_M$. This gives a combinatorial expression for the degree of an arbitrary torus orbit closure in the Grassmannian $Gr_{k,n}$. We then derive analogous results for the independent set polytope and the associated flag matroid polytope of $M$. Our proofs are based on a natural extension of Postnikov's theory of generalized permutohedra. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
90
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(92 citation statements)
references
References 0 publications
2
90
0
Order By: Relevance
“…Towards the conjecture we prove in Theorem 4.5 that the linear coefficient for any generalized permutahedron is indeed nonnegative. 1 As an application, we then obtain an inequality among beta invariants of contractions of any given matroid in Corollary 4.7 using a result of Ardila, Benedetti and Doker [3]. We also apply our results to solid-angle polynomials and show the existence of a three dimensional generalized permutahedron whose solid-angle polynomial has negative linear term.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…Towards the conjecture we prove in Theorem 4.5 that the linear coefficient for any generalized permutahedron is indeed nonnegative. 1 As an application, we then obtain an inequality among beta invariants of contractions of any given matroid in Corollary 4.7 using a result of Ardila, Benedetti and Doker [3]. We also apply our results to solid-angle polynomials and show the existence of a three dimensional generalized permutahedron whose solid-angle polynomial has negative linear term.…”
Section: Introductionmentioning
confidence: 90%
“…We say that i y i P i defines a polytope if P = i : y i <0 (−y i )P i is a Minkowski summand of Q = i : y i ≥0 y i P i , in which case i y i P i represents the Minkowski difference Q−P . In [3], Ardila, Benedetti and Doker showed that every generalized permutahedron has a unique expression as a signed Minkowski sum of standard simplices. By a result of Shephard, Minkowski summands of polytopes can be characterized in terms of their edge directions and edge lengths (see [21, p. 318]).…”
Section: Signed Minkowski Sumsmentioning
confidence: 99%
See 2 more Smart Citations
“…In [7] Castillo and Liu conjectured something stronger regarding Ehrhart positivity: that all generalized permutohedra are Ehrhart positive. The validity of that conjecture implies that all matroids are Ehrhart positive, since it is known that matroid polytopes are a subfamily of generalized permutohedra (see for example [1]).…”
Section: Introductionmentioning
confidence: 96%